2014
DOI: 10.1111/plb.12270
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, structural and molecular traits activated in strawberry plants after inoculation with the plant growth‐promoting bacterium Azospirillum brasilense REC3

Abstract: The plant growth-promoting strain REC3 of Azospirillum brasilense, isolated from strawberry roots, prompts growth promotion and systemic protection against anthracnose disease in this crop. Hence, we hypothesised that A. brasilense REC3 can induce different physiological, structural and molecular responses in strawberry plants. Therefore, the aim of this work was to study these traits activated in Azospirillum-colonised strawberry plants, which have not been assessed until now. Healthy, in vitro micropropagate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Ellagitannins have been shown to accumulate upon foliar application of benzothiadiazole ( Hukkanen et al, 2007 ) or the pathogen Colletotrichum fragariae ( Mamani et al, 2012 ). Benzothiadiazole is a plant defense elicitor compound that activates systemic acquired resistance (SAR; Hukkanen et al, 2007 ; Guerrero-Molina et al, 2014 ; Karlund et al, 2014 ), which in turn provides protection against a number of foliar pathogens, including X. fragariae, S. macularis, B. cinerea and C. acutatum ( Terry and Joyce, 2000 ; Hukkanen et al, 2007 ; Merteley, 2010 ; Grellet-Bournonville et al, 2012 ; Braun and Hildebrand, 2013 ). Interestingly, infection with X. fragariae was recently found to decrease concentrations of ellagitannin and gallotannin in strawberry leaves ( Kim et al, 2016 ) and it is possible that suppression of the synthesis of these compounds is a key virulence mechanism ( Ishikawa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ellagitannins have been shown to accumulate upon foliar application of benzothiadiazole ( Hukkanen et al, 2007 ) or the pathogen Colletotrichum fragariae ( Mamani et al, 2012 ). Benzothiadiazole is a plant defense elicitor compound that activates systemic acquired resistance (SAR; Hukkanen et al, 2007 ; Guerrero-Molina et al, 2014 ; Karlund et al, 2014 ), which in turn provides protection against a number of foliar pathogens, including X. fragariae, S. macularis, B. cinerea and C. acutatum ( Terry and Joyce, 2000 ; Hukkanen et al, 2007 ; Merteley, 2010 ; Grellet-Bournonville et al, 2012 ; Braun and Hildebrand, 2013 ). Interestingly, infection with X. fragariae was recently found to decrease concentrations of ellagitannin and gallotannin in strawberry leaves ( Kim et al, 2016 ) and it is possible that suppression of the synthesis of these compounds is a key virulence mechanism ( Ishikawa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study conducted by Tomas-Grau [12] demonstrates that in strawberry, the oxidative burst is extended to the whole leaflet in control plants, whereas it is restricted to the lesion area in the case of MS-treated plants. In addition, this study also revealed an up-regulation of the FaCAT gene that encodes a catalase in the strawberry plant [30], which could explain the low H2O2 accumulation observed 48 h after MS treatment.…”
Section: Oxidative Stressmentioning
confidence: 53%
“…Previous studies reported that combination of PGPR with D r a f t various seed priming approaches including hydropriming, osmopriming or redox priming resulted in better plant performance. But the bacterial cell density and seed priming durations had wide ranges from 10 6 -10 9 CFU/mL and 8-24 h (Carrozzi et al 2012;Zulueta-Rodríguez et al 2015;Jafariyan and Zarea 2016) maybe because of different plant species or seed characteristics (Liu et al 2016). In the present study, an optimal seed priming reagent, a more precise bacterial cell density and seed priming time were obtained, which is crucial for practical application of the co-treatment.…”
Section: R a F Tmentioning
confidence: 64%